CAPACITY BUILDING CIVITAS AKADEMIKA STAI AL HUSAIN DALAM PEMANFAATAN SISTEM INFORMASI AKADEMIK - Fatkhul Ngali; Nur Latifah (khidmatan, 2021)
Good academic civitas data processing will make the reporting needed by the  appropriate database to process policies such as national diploma numbering (PIN), this is very much needed to minimize cases of diploma forgery that are rife, to complete and report appropriate civitas data, there must be optimal facilities, infrastructure, and resources. The purpose of this service is to find out the optimization of data processing for the STAI Al Husain academic community with the academic information system (SIAKAD) through mentoring activities with the ABCD approach, this approach is to empower existing assets. In carrying out an ABCD-based approach, we must look for the availability of assets, and synchronization with the role of the academic community to measure the success of ABCD. The data processing and reporting activities of the academic community that are accompanied have basically produced results, such as the data is appropriate, and the reporting is appropriate. However, they still find the role of the community who still do not understand well about Siakad and still need assistance.